3kW circulating fluidized bed chemical looping reactor - A thermochemical and chemomechanical investigation on the performance of Cu- impregnated Al2O3 as an oxygen carrier material. (July 2021) - Pishahang, Mehdi; Larring, Yngve; Stensrød, Ruth E; Andreassen, Kari A; Spjelkavik, Aud I
Highlights: Redox performance of Cu–Al2O3 as an OCM for CLC is investigated. A novel 3kWth circulating fluidized bed CLC reactor is developed. Loose elemental Cu islands on top of the OCM are responsible for high rate of hot attrition at the beginning. Once those are removed the CuAl2O4 shows a much better attrition performance. Full combustion of methane using this OCM was achieved. Abstract: Among Oxygen Carrier Materials (OCM) for Chemical Looping Combustion (CLC) using solid and gaseous fuels, copper oxide supported on alumina is one of the most promising systems. This work presents a comprehensive study on redox and chemo-mechanical performance of this material through thermogravimetry analysis, micro fixed bed reactor and a 3 kW circulating fluidized bed reactor. Chemical looping with oxygen uncoupling (CLOU) behavior, oxygen transfer capacity, reactivity with methane, and attrition rates were analyzed. The cold and hot attrition performance of the OCM was analyzed, based on which lifetime of the OCM under redox condition was estimated.